Boron nitride nanosheet coated spherical oxide core-shell structure composite material as well as preparation method and application thereof
By growing boron -nitride tablets on the surface of the spherical oxide to form a composite material of nuclear shell structure, the problem of lack of coating and refrigeration performance formed by the existing technologies to directly add the coatings. High -efficiency thermal management and hydrophobicity.
Patent Information
- Application Number
- CN202411574882.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, boron nitride nanoparticles are directly added to the coating formed in the coating, and the radiation refrigeration performance has not yet achieved the best effect.
By mixing boron sources, magnesium oxide, and tetralet oxide, the boron -containing front drive body is formed, and the spherical oxide is scattered in the alcohol solvent to form a spherical oxide dispersed liquid. Boronimlon tablets are evenly growing on the surface of the spherical oxide, forming a composite material of the spherical oxide riblon in the spherical oxide ribronic.
It improves the thermal management performance of the coating, shows good radiation refrigeration characteristics, and gives coating strong hydrophobicity, has anti -decoration and self -cleaning properties.
Smart Images

Figure CN119370873A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of material technology, and in particular to a boron nitride nanosheet-coated spherical oxide core-shell structure composite material, a preparation method and application thereof. Background Art
[0002] Passive radiative cooling technology is a technology that does not require electricity or refrigerants, but achieves cooling by reflecting sunlight and radiating heat into outer space. It can be used to cool buildings and outdoor equipment. Passive radiative cooling technology has the advantages of low carbon and low energy consumption. It is a promising thermal management strategy to solve the problem of global warming and has received widespread attention in recent years. Constructing a coating with radiative cooling properties can significantly reduce the use of traditional high-energy consumption equipment, thereby reducing carbon emissions.
[0003] Boron nitride materials with two-dimensional structures have been widely studied due to their extremely high thermal conductivity, excellent insulation and chemical stability. In addition, boron nitride has a suitable band gap and unique morphology, has a high solar reflectivity, and can be used in passive radiation cooling technology. The spatial distribution of boron nitride within the system will greatly affect the overall thermal management properties of the material. The current related technologies usually directly use boron nitride nanoparticles as raw materials, add boron nitride nanoparticles to the coating, and then form a coating through coating and curing. The radiation cooling performance of the coating formed in this way needs to be improved. Summary of the invention
[0004] In view of this, the present invention provides a composite material of a core-shell structure of boron nitride nanosheets coated with a spherical oxide, and a preparation method and application thereof. In the core-shell structure composite material provided by the present invention, boron nitride nanosheets are densely and evenly grown on the surface of the spherical oxide, and the coating formed by the core-shell material has excellent thermal management performance and exhibits good radiation cooling characteristics.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] A method for preparing a composite material of a spherical oxide core-shell structure coated with boron nitride nanosheets comprises the following steps:
[0007] mixing a boron source, magnesium oxide and ferrosoferric oxide to obtain a boron-containing precursor;
[0008] dispersing the spherical oxide in an alcohol solvent to obtain a spherical oxide dispersion;
[0009] The spherical oxide dispersion is coated on the surface of a substrate and then dried to obtain a substrate loaded with a spherical oxide coating;
[0010] The substrate loaded with the spherical oxide coating is placed on the boron-containing precursor, and then heat treated to obtain the boron nitride nanosheet-coated spherical oxide core-shell structure composite material.
[0011] Preferably, the boron source includes one or more of boron powder, boron oxide and boric acid.
[0012] Preferably, the molar ratio of the boron source, magnesium oxide and ferrosoferric oxide is 1:0.3-0.7:0.1-0.5; the mixing is grinding mixing, and the grinding mixing time is 5-10 minutes.
[0013] Preferably, the spherical oxide comprises one or more of alumina microspheres and silica microspheres; the diameter of the spherical oxide is 1 to 10 μm; the alcohol solvent is ethanol; and the dosage ratio of the spherical oxide to the alcohol solvent is 0.4 to 1.4 mmol: 0.5 to 3 mL.
[0014] Preferably, the substrate is a silicon wafer or an alumina ceramic wafer; the coating amount of the spherical oxide dispersion is 0.03-0.5 mL / cm 2 ;
[0015] The substrate carrying the spherical oxide coating is placed horizontally above the boron-containing precursor.
[0016] Preferably, the heat treatment includes a heating stage, a heat preservation stage and a cooling stage; the protective gas in the heating stage is nitrogen or an inert gas, and the heating rate is 3 to 8°C / min; the protective gas in the heat preservation stage is a nitrogen-containing gas, the heat preservation temperature is 1000 to 1300°C, and the heat preservation time is 0.5 to 2h; the nitrogen-containing gas is ammonia or a mixture of nitrogen and hydrogen; the protective gas in the cooling stage is nitrogen or an inert gas, and the cooling rate is 3 to 8°C / min.
[0017] Preferably, after the heat treatment, a boron nitride nanosheet-coated spherical oxide core-shell structure composite material coating is obtained on the surface of the substrate; and the process also includes scraping and collecting the coating to obtain a boron nitride nanosheet-coated spherical oxide core-shell structure composite material powder.
[0018] The present invention also provides a boron nitride nanosheet-coated spherical oxide core-shell structure composite material prepared by the preparation method described in the above scheme, comprising a core and a shell coated on the surface of the core; the core is a spherical oxide, and the shell is a boron nitride nanosheet.
[0019] Preferably, the boron oxide nanosheets have a lateral size of 150 to 350 nm and a thickness of 20 to 40 nm.
[0020] The present invention also provides the application of the composite material of boron nitride nanosheets coated spherical oxide core-shell structure described in the above scheme in thermal management.
[0021] The present invention provides a method for preparing a composite material of a core-shell structure of a spherical oxide coated with a boron nitride nanosheet, comprising the following steps: mixing a boron source, magnesium oxide and ferroferric oxide to obtain a boron-containing precursor; dispersing the spherical oxide in an alcohol solvent to obtain a spherical oxide dispersion; coating the spherical oxide dispersion on a substrate surface and drying to obtain a substrate loaded with a spherical oxide coating; placing the substrate loaded with a spherical oxide coating on top of the boron-containing precursor, and then performing a heat treatment to obtain the composite material of a core-shell structure of a spherical oxide coated with a boron nitride nanosheet. The present invention uses a spherical oxide with a three-dimensional structure as a matrix, and forms a uniform three-dimensional core-shell configuration material by growing boron nitride nanosheets on the surface, which can enhance the interface bonding between the two, improve the heat transmission efficiency inside the three-dimensional network structure composite material, and thus improve the thermal management performance of the coating, presenting good radiation cooling characteristics. In addition, boron nitride nanosheets have excellent chemical stability and strong hydrophobicity, which can make the coating highly hydrophobic, giving the coating anti-fouling and self-cleaning properties. They can play an important role in anti-corrosion, anti-water aggregation and fog condensation systems, and meet the coating use requirements in a variety of environments.
[0022] The present invention places a substrate loaded with a spherical oxide coating on top of a boron-containing precursor, and uniformly grows boron nitride nanosheets on the surface of the spherical oxide through heat treatment, thereby forming a spherical core-shell structure coated with high-purity boron nitride nanosheets. The volatilization growth of the precursor during the heat treatment process can avoid the introduction of impurity ions and the influence on the morphology of the boron nitride nanosheets, thereby ensuring the purity and uniformity of the boron nitride nanosheets. In addition, the present invention uses low-cost raw materials, and can prepare a composite material of a spherical oxide core-shell structure coated with boron nitride nanosheets only through operations such as mixing, coating, and heat treatment. The method is simple, easy to operate, and can be replicated in large quantities to achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a low-magnification scanning electron microscope image of the boron nitride nanosheet-coated spherical alumina core-shell structure composite material powder prepared in Example 1;
[0024] Figure 2 This is a high-magnification scanning electron microscope image of the boron nitride nanosheet-coated spherical alumina core-shell structure composite material powder prepared in Example 1;
[0025] Figure 3 This is a high-resolution transmission image of boron nitride nanosheets in the boron nitride nanosheet-coated spherical alumina core-shell structure composite material powder prepared in Example 1;
[0026] Figure 4 The XRD spectrum of the boron nitride nanosheet-coated spherical alumina core-shell structure composite material powder prepared in Example 1;
[0027] Figure 5 This is the water contact angle of the boron nitride nanosheet-coated spherical alumina core-shell structure composite coating prepared in Example 1.
[0028] Figure 6 This is the outdoor test temperature curve of the cavity formed by the boron nitride nanosheets coated spherical alumina core-shell structure composite coating prepared in Example 1. DETAILED DESCRIPTION
[0029] The present invention provides a method for preparing a composite material of a spherical oxide core-shell structure coated with boron nitride nanosheets, comprising the following steps:
[0030] mixing a boron source, magnesium oxide and ferrosoferric oxide to obtain a boron-containing precursor;
[0031] dispersing the spherical oxide in an alcohol solvent to obtain a spherical oxide dispersion;
[0032] The spherical oxide dispersion is coated on the surface of a substrate and then dried to obtain a substrate loaded with a spherical oxide coating;
[0033] The substrate loaded with the spherical oxide coating is placed on the boron-containing precursor, and then heat treated to obtain the boron nitride nanosheet-coated spherical oxide core-shell structure composite material.
[0034] The boron source, magnesium oxide and ferroferric oxide are mixed to obtain a boron-containing precursor. In the present invention, the boron source preferably includes one or more of boron powder, boron oxide and boric acid; the purity of the boron powder is preferably above 98%; the molar ratio of the boron source, magnesium oxide and ferroferric oxide is preferably 1:0.3-0.7:0.1-0.5, more preferably 1:0.5-0.6:0.15-0.3; the mixing is preferably grinding mixing, and the grinding mixing time is preferably 5-10 minutes; the grinding mixing is preferably carried out in an agate mortar; the addition of magnesium oxide and ferroferric oxide in the present invention can increase the reactive boron oxide (B x O y )The accumulation of vapor pressure is beneficial to the nucleation and growth of boron nitride nanosheets.
[0035] The present invention disperses spherical oxides in an alcohol solvent to obtain a spherical oxide dispersion. In the present invention, the spherical oxides preferably include one or more of aluminum oxide microspheres and silicon oxide microspheres; the diameter of the spherical oxides is preferably 1 to 10 μm; the alcohol solvent is preferably ethanol; the dosage ratio of the spherical oxides to the alcohol solvent is preferably 0.4 to 1.4 mmol: 0.5 to 3 mL, specifically 0.5 mmol: 2 mL, 1 mmol: 2 mL, 1.5 mmol: 2 mL or 1.4 mmol: 3 mL; the dispersion is preferably carried out under ultrasonic and stirring conditions, and the dispersion time is preferably 20 to 40 min.
[0036] After obtaining the spherical oxide dispersion, the present invention applies the spherical oxide dispersion on the surface of the substrate and then dries it to obtain a substrate loaded with a spherical oxide coating. In the present invention, the substrate is preferably a silicon wafer or an alumina ceramic wafer, specifically a commercial silicon wafer or a commercial alumina ceramic wafer, the length of the silicon wafer is preferably 60 to 100 mm, the width is preferably 10 to 30 mm, and the height is preferably 400 to 600 μm, and the silicon wafer is preferably a double-sided polished silicon wafer; the length of the alumina ceramic wafer is preferably 20 to 50 mm, the width is preferably 20 to 50 mm, and the height is preferably 0.5 to 1.5 mm; in an embodiment of the present invention, the spherical oxide dispersion is specifically applied on one side of the substrate; the substrate is preferably washed alternately with anhydrous ethanol and deionized water before coating, and then dried for standby use; the coating amount of the spherical oxide dispersion is preferably 0.03 to 0.5 mL / cm 2 , more preferably 0.06 to 0.25 mL / cm 2 The present invention has no special requirements for the drying conditions, as long as the wet coating obtained by coating can be dried.
[0037] After obtaining the substrate loaded with spherical oxide coating, the present invention places the substrate loaded with spherical oxide coating on top of the boron-containing precursor, and then performs heat treatment to obtain the boron nitride nanosheet-coated spherical oxide core-shell structure composite material. In the present invention, the molar ratio of the spherical oxide in the spherical oxide coating to the boron source in the boron-containing precursor is preferably 0.5-1.5:0.75; the substrate loaded with spherical oxide coating is placed horizontally on top of the boron-containing precursor, and the coating surface faces downward.
[0038] In the present invention, the heat treatment preferably includes a heating stage, a heat preservation stage and a cooling stage; the protective gas in the heating stage is preferably nitrogen or an inert gas, the inert gas is preferably argon, and the heating rate in the heating stage is preferably 3-8°C / min, more preferably 5°C / min; the protective gas in the heat preservation stage is preferably a nitrogen-containing gas, the nitrogen-containing gas is preferably ammonia or a mixture of nitrogen and hydrogen, and the volume ratio of nitrogen to hydrogen in the mixture of nitrogen and hydrogen is preferably 95% to 5%; the heat preservation temperature in the heat preservation stage is preferably 1000-1300°C, more preferably 1200°C, and the heat preservation time in the heat preservation stage is preferably 0.5-2h, more preferably 1h; the protective gas in the cooling stage is preferably nitrogen or an inert gas, the inert gas is preferably argon, and the cooling rate in the cooling stage is preferably 3-8°C / min, more preferably 5°C / min.
[0039] In a specific embodiment of the present invention, it is preferred to first place the boron-containing precursor in an alumina porcelain boat, and then place the substrate loaded with the spherical oxide coating horizontally on the surface of the boron-containing precursor in the porcelain boat, and then place the porcelain boat in a tube furnace for heat treatment; before the heat treatment, it is preferred to first use a vacuum pump to evacuate the furnace chamber to a vacuum state, and fill it with the protective gas required for the heating stage, repeat the process of evacuating and filling with the protective gas 2 to 4 times, and then start heating. After heating to the temperature of the insulation stage, replace the gas in the tube furnace with a nitrogen-containing gas. After the insulation stage is over, replace the gas in the tube furnace with the protective gas required for the cooling stage again until it cools to room temperature.
[0040] During the heat treatment process, the boron source and the nitrogen-containing gas react to generate boron nitride nanosheets and coat the surface of the spherical oxide, forming a boron nitride nanosheet-coated spherical oxide core-shell structure composite material coating on the substrate surface. The coating is scraped off and collected to obtain a boron nitride nanosheet-coated spherical oxide core-shell structure composite material powder; in the specific implementation process of the present invention, the powder can be used as a filler in a polymer.
[0041] The present invention also provides a boron nitride nanosheet-coated spherical oxide core-shell structure composite material prepared by the preparation method described in the above scheme, comprising a core and a shell coated on the surface of the core; the core is a spherical oxide, and the shell is a boron nitride nanosheet. In the present invention, the lateral size of the boron oxide nanosheet is preferably 150 to 350 nm, and the thickness is preferably 20 to 40 nm.
[0042] The present invention also provides the application of the boron nitride nanosheet-coated spherical oxide core-shell structure composite material described in the above scheme in thermal management; in the present invention, the thermal management method is specifically radiative cooling.
[0043] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Example 1
[0045] 7.5 mmol of boron powder (purity of 98%), 3.75 mmol of magnesium oxide and 1.25 mmol of ferrosoferric oxide were placed in an agate mortar in sequence and ground evenly for 5 minutes to obtain a boron-containing precursor.
[0046] 1 mmol of commercial alumina microspheres was dispersed in 2 mL of anhydrous ethanol, and ultrasonicated and stirred for 30 minutes to obtain an alumina microsphere dispersion, wherein the particle size of the commercial alumina microspheres was 1 to 10 μm.
[0047] A commercial alumina ceramic sheet with a length × width × height of 30 mm × 30 mm × 0.5 mm was used as a substrate. The substrate was alternately cleaned with anhydrous ethanol and deionized water and dried for standby use. Then, 2 mL of the above-mentioned alumina microsphere dispersion was evenly coated on the surface of the substrate and then dried to obtain a substrate loaded with an alumina microsphere coating.
[0048] The boron-containing precursor was transferred to an alumina porcelain boat, and the substrate loaded with the alumina microsphere coating was placed horizontally above the boron-containing precursor in the porcelain boat. The porcelain boat was then placed in a tubular furnace, and the furnace chamber was evacuated to a vacuum state using a vacuum pump and filled with nitrogen. This process was repeated twice.
[0049] The tubular furnace was heated to 1200°C at a rate of 5°C / min under a nitrogen atmosphere. After the heating was completed, the furnace chamber atmosphere was replaced with ammonia and kept warm for 1 hour. After the insulation was completed, the furnace chamber protective atmosphere was replaced with nitrogen again. The furnace was cooled to room temperature at a cooling rate of 5°C / min to obtain a coating of alumina microspheres coated with boron nitride nanosheets supported on alumina ceramic sheets. Spherical alumina core-shell structure composite material powders coated with boron nitride nanosheets were obtained by scraping and collecting.
[0050] Example 2
[0051] 3.75 mmol of boric acid, 3.75 mmol of magnesium oxide and 1.25 mmol of ferrosoferric oxide were placed in an agate mortar in sequence and ground evenly for 5 minutes to obtain a boron-containing precursor.
[0052] 1 mmol of commercial alumina microspheres was dispersed in 2 mL of anhydrous ethanol, and ultrasonicated and stirred for 30 minutes to obtain an alumina microsphere dispersion, wherein the particle size of the commercial alumina microspheres was 1 to 10 μm.
[0053] A commercial silicon wafer with dimensions of 100 mm × 20 mm × 500 μm in length × width × height was used as a substrate. The substrate was alternately cleaned with anhydrous ethanol and deionized water and dried for standby use. Then, 2 mL of the above-mentioned alumina microsphere dispersion was evenly coated on the surface of the carrier and then dried to obtain a substrate loaded with an alumina microsphere coating.
[0054] The boron-containing precursor was transferred to an alumina porcelain boat, and the substrate loaded with the alumina microsphere coating was placed horizontally above the boron-containing precursor in the porcelain boat. The porcelain boat was then placed in a tubular furnace, and the furnace chamber was evacuated to a vacuum state using a vacuum pump and filled with nitrogen. This process was repeated twice.
[0055] The tubular furnace was heated to 1100°C at a rate of 5°C / min under a nitrogen atmosphere. After the heating was completed, the furnace chamber atmosphere was replaced with ammonia and kept warm for 1 hour. After the insulation was completed, the furnace chamber protective atmosphere was replaced with nitrogen again. The furnace was cooled to room temperature at a cooling rate of 5°C / min to obtain a silicon wafer-loaded boron nitride nanosheet-coated alumina microsphere core-shell structure composite coating. The boron nitride nanosheet-coated spherical alumina core-shell structure composite powder was obtained by scraping and collecting.
[0056] Example 3
[0057] 7.5 mmol of boron powder (purity of 98%), 3.75 mmol of magnesium oxide and 1.25 mmol of ferrosoferric oxide were placed in an agate mortar in sequence and ground evenly for 5 minutes to obtain a boron-containing precursor.
[0058] 0.5 mmol of commercial silica microspheres were dispersed in 2 mL of anhydrous ethanol, and ultrasonicated and stirred for 30 minutes to obtain a silica microsphere dispersion, wherein the particle size of the commercial silica microspheres was 1 to 10 μm.
[0059] A commercial alumina ceramic sheet with a length × width × height of 30 mm × 30 mm × 1 mm was used as a substrate. The substrate was alternately cleaned with anhydrous ethanol and deionized water and dried for standby use. Then, 2 mL of the above-mentioned silica microsphere dispersion was evenly coated on the surface of the substrate, and then dried to obtain a substrate loaded with a silica microsphere coating.
[0060] The precursor containing boron was transferred to an alumina porcelain boat, and the carrier loaded with the silica microsphere coating was horizontally placed above the precursor A in the porcelain boat. The porcelain boat was then placed in a tube furnace, and the furnace chamber was evacuated to a vacuum state using a vacuum pump and filled with nitrogen. This process was repeated twice;
[0061] Step 5, heating the tubular furnace to 1200°C at a rate of 5°C / min under a nitrogen atmosphere, replacing the furnace chamber atmosphere with ammonia after heating and keeping it warm for 1 hour, replacing the furnace chamber protective atmosphere with nitrogen again after calcination, cooling to room temperature at a cooling rate of 5°C / min, and obtaining a coating of a composite material of boron nitride nanosheets coated with silicon oxide microspheres core-shell structure supported by alumina ceramic sheets, and obtaining a boron nitride nanosheet-coated spherical silicon oxide core-shell structure composite material powder by scraping and collecting.
[0062] Example 4
[0063] 9 mmol boron powder (purity of 98%), 5 mmol magnesium oxide and 2.7 mmol ferrosoferric oxide were placed in an agate mortar in sequence and ground evenly for 5 minutes to obtain a boron-containing precursor.
[0064] 1.5 mmol of commercial alumina microspheres were dispersed in 2 mL of anhydrous ethanol, and ultrasonicated and stirred for 30 minutes to obtain an alumina microsphere dispersion, wherein the particle size of the commercial alumina microspheres was 1 to 10 μm.
[0065] A commercial silicon wafer with dimensions of 100 mm × 30 mm × 500 μm in length × width × height was used as a substrate. The substrate was alternately cleaned with anhydrous ethanol and deionized water and dried for standby use. Then, 2 mL of the above-mentioned alumina microsphere dispersion was evenly coated on the surface of the substrate, and then dried to obtain a substrate loaded with an alumina microsphere coating.
[0066] The boron-containing precursor was transferred to an alumina porcelain boat, and the substrate loaded with the alumina microsphere coating was placed horizontally above the boron-containing precursor in the porcelain boat. The porcelain boat was then placed in a tubular furnace, and the furnace chamber was evacuated to a vacuum state using a vacuum pump and filled with argon. This process was repeated twice.
[0067] The tubular furnace was heated to 1150°C at a rate of 5°C / min under an argon atmosphere. After the heating was completed, the furnace chamber atmosphere was replaced with ammonia and kept warm for 2 hours. After the insulation was completed, the furnace chamber protective atmosphere was replaced with argon again. The furnace was cooled to room temperature at a cooling rate of 5°C / min to obtain a silicon wafer-loaded boron nitride nanosheet-coated alumina microsphere core-shell structure composite coating. The boron nitride nanosheet-coated spherical alumina core-shell structure composite powder was obtained by scraping and collecting.
[0068] Example 5
[0069] 7.5 mmol of boron powder (purity of 98%), 3.75 mmol of magnesium oxide and 1.25 mmol of ferrosoferric oxide were placed in an agate mortar in sequence and ground evenly for 5 minutes to obtain a boron-containing precursor.
[0070] 1.4 mmol of commercial alumina microspheres were dispersed in 3 mL of anhydrous ethanol, and ultrasonicated and stirred for 30 min to obtain an alumina microsphere dispersion, wherein the particle size of the commercial silicon oxide microspheres was 1 to 10 μm.
[0071] A commercial alumina ceramic sheet with a length × width × height of 40 mm × 40 mm × 0.5 mm was used as a substrate. The substrate was alternately cleaned with anhydrous ethanol and deionized water and dried for standby use. Then, 3 mL of the above-mentioned silica microsphere dispersion was evenly coated on the surface of the substrate, and then dried to obtain a substrate loaded with alumina microsphere coating.
[0072] The boron-containing precursor was transferred to an alumina porcelain boat, and the substrate loaded with the alumina microsphere coating was placed horizontally above the boron-containing precursor in the porcelain boat. The porcelain boat was then placed in a tubular furnace, and the furnace chamber was evacuated to a vacuum state using a vacuum pump and filled with nitrogen. This process was repeated twice.
[0073] The tubular furnace was heated to 1200°C at a rate of 5°C / min under a nitrogen atmosphere. After the heating was completed, the furnace chamber atmosphere was replaced with ammonia and kept warm for 2 hours. After the calcination was completed, the furnace chamber protective atmosphere was replaced with nitrogen again. The furnace was cooled to room temperature at a cooling rate of 5°C / min to obtain a coating of alumina microsphere core-shell structure composite material coated with boron nitride nanosheets supported on alumina ceramic sheets. Spherical alumina core-shell structure composite material powder coated with boron nitride nanosheets was obtained by scraping and collecting.
[0074] Characterization and performance testing:
[0075] 1. Characterization
[0076] Figure 1 This is a low-magnification scanning electron microscope image of the boron nitride nanosheet-coated spherical alumina core-shell structure composite material powder prepared in Example 1; Figure 2 This is a high-magnification scanning electron microscope image of the boron nitride nanosheet-coated spherical alumina core-shell structure composite material powder prepared in Example 1. Figure 1-2 It can be seen that the boron nitride nanosheets grow densely and evenly on the surface of the three-dimensional spherical oxide. The lateral size of the boron nitride nanosheets is 150-350nm and the thickness is 20-40nm. The boron nitride nanosheets grown evenly on the surface are matched with the spherical oxide to form a three-dimensional interconnected internal configuration, which can improve the heat transfer efficiency inside the three-dimensional network structure composite material, thereby improving the thermal management performance of the material and making the material exhibit better radiation cooling characteristics.
[0077] Figure 3 This is a high-resolution transmission image of the boron nitride nanosheets in the boron nitride nanosheet-coated spherical alumina core-shell structure composite material powder prepared in Example 1. Figure 3It can be seen that the high-resolution lattice fringe spacing is about 0.35 nm, corresponding to the (002) crystal plane of the boron nitride nanosheets, further confirming the synthesis of the boron nitride nanosheets.
[0078] Figure 4 This is the XRD spectrum of the boron nitride nanosheet-coated spherical alumina core-shell structure composite material powder prepared in Example 1. Figure 4 It can be seen that compared with single alumina, the three-dimensional core-shell boron nitride nanosheets coated alumina sample showed two diffraction peaks at 26.4° and 41.6°, corresponding to the (002) crystal plane and (100) crystal plane of boron nitride, respectively, proving the formation of a composite material.
[0079] Figure 5 The water contact angle of the boron nitride nanosheet-coated spherical alumina core-shell structure composite coating prepared in Example 1. Figure 5 It can be seen that the water contact angle of the coating surface is about 149.7°, showing excellent hydrophobic properties. This property gives the coating anti-fouling and self-cleaning properties, which can meet the use requirements in a variety of environments.
[0080] 2. Thermal management performance test
[0081] The boron nitride nanosheet-coated spherical alumina core-shell structure composite coating prepared in Example 1 was subjected to outdoor testing, and an alumina ceramic sheet without coating was used as a comparison. The specific scheme is as follows:
[0082] A polystyrene foam box was used as the insulation material. A rectangular opening of the same size of 3.5cm×3.5cm×3.5cm was made on the top of the box. The constructed coating material and the alumina substrate were placed at the opening. In order to reduce the absorption of sunlight, the outside of the foam box was evenly wrapped with aluminum foil; the top of the equipment was covered with a polyethylene film at a certain height to reduce the influence of the surrounding environment of the test point on heat convection and heat conduction. The test device was placed on the ground with sufficient sunlight and no shielding. During the test, a solar power meter was used to record the solar irradiance, and a multi-channel temperature tester was used to record the real-time temperature of the test point and the environment.
[0083] Figure 6 This is the outdoor test temperature curve of the cavity formed by the boron nitride nanosheets coated spherical alumina core-shell structure composite coating prepared in Example 1. Figure 6 It can be seen that the cavity temperature with the core-shell structure composite material coating of the present invention is lower, about 6.2° C. lower than the temperature of the cavity of the alumina ceramic sheet, indicating that the core-shell structure composite material of the present invention has excellent radiation cooling performance.
[0084] The same test was performed on the core-shell structure composite material coatings and powders prepared in Examples 2 to 5. The results showed that the boron nitride nanosheets grew densely and evenly on the surface of the spherical oxide, and the obtained coatings had excellent radiative cooling performance.
[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a composite material of a spherical oxide core-shell structure coated with boron nitride nanosheets, characterized in that: The following steps are involved: mixing a boron source, magnesium oxide and ferrosoferric oxide to obtain a boron-containing precursor; dispersing the spherical oxide in an alcohol solvent to obtain a spherical oxide dispersion; The spherical oxide dispersion is coated on the surface of a substrate and then dried to obtain a substrate loaded with a spherical oxide coating; The substrate loaded with the spherical oxide coating is placed on the boron-containing precursor, and then heat treated to obtain the boron nitride nanosheet-coated spherical oxide core-shell structure composite material.
2. The preparation method according to claim 1, characterized in that: The boron source includes one or more of boron powder, boron oxide and boric acid.
3. The preparation method according to claim 1, characterized in that: The molar ratio of the boron source, magnesium oxide and ferrosoferric oxide is 1:0.3-0.7:0.1-0.5; the mixing is grinding mixing, and the grinding mixing time is 5-10 minutes.
4. The preparation method according to claim 1, characterized in that: The spherical oxide comprises one or more of aluminum oxide microspheres and silicon oxide microspheres; the diameter of the spherical oxide is 1 to 10 μm; the alcohol solvent is ethanol; the dosage ratio of the spherical oxide to the alcohol solvent is 0.4 to 1.5 mmol: 0.5 to 3 mL.
5. The preparation method according to claim 1, characterized in that: The substrate is a silicon wafer or an alumina ceramic wafer; the coating amount of the spherical oxide dispersion is 0.03-0.5 mL / cm 2 ; The substrate carrying the spherical oxide coating is placed horizontally above the boron-containing precursor.
6. The preparation method according to claim 1, characterized in that: The heat treatment includes a heating stage, a heat preservation stage and a cooling stage; the protective gas in the heating stage is nitrogen or an inert gas, and the heating rate is 3 to 8°C / min; the protective gas in the heat preservation stage is a nitrogen-containing gas, the heat preservation temperature is 1000 to 1300°C, and the heat preservation time is 0.5 to 2h; the nitrogen-containing gas is ammonia or a mixture of nitrogen and hydrogen; the protective gas in the cooling stage is nitrogen or an inert gas, and the cooling rate is 3 to 8°C / min.
7. The preparation method according to claim 1, characterized in that: After the heat treatment, a boron nitride nanosheet-coated spherical oxide core-shell structure composite material coating is obtained on the substrate surface; the method also includes scraping and collecting the coating to obtain a boron nitride nanosheet-coated spherical oxide core-shell structure composite material powder.
8. A boron nitride nanosheet-coated spherical oxide core-shell structure composite material prepared by the preparation method according to any one of claims 1 to 7, comprising a core and a shell coated on the surface of the core; the core is a spherical oxide, and the shell is a boron nitride nanosheet.
9. The boron nitride nanosheet-coated spherical oxide core-shell structure composite material according to claim 8, characterized in that: The boron oxide nanosheet has a lateral size of 150 to 350 nm and a thickness of 20 to 40 nm.
10. Use of the boron nitride nanosheet-coated spherical oxide core-shell structure composite material according to claim 8 or 9 in thermal management.
Citation Information
Cited By
Ceramic matrix composite (CMC) and preparation method thereof
CN121292982A